Effect of different fibers on small-strain dynamic properties of microbially induced calcite precipitation–fiber combined reinforced calcareous sand. (7th March 2022) - Shan, Yi; Liang, Junling; Tong, Huawei; Yuan, Jie; Zhao, Jitong
Highlights: Small-strain dynamic properties of polyester and hemp MICP-fiber combined reinforced calcareous sand were studied. The maximum dynamic shear modulus is positively correlated with the calcium carbonate with the increase of fiber content. Fibers and its content accelerate the stiffness degradation of MICP cemented calcareous sand based on the bonding between fibers and calcareous sand. Hemp fiber with rougher surface results in greater damping ratio of MICP cemented calcareous sand than polyester fiber by AFM test. Abstract: Microbially induced calcite precipitation (MICP)–fiber combined reinforcement through the addition of fibers during the MICP process is a novel, natural, and green technique for foundation improvement, which can effectively enhance the mechanical properties of cemented soil. However, the small-strain dynamic properties of this method remain unexplored. The effects of different polyester fiber and hemp fiber contents (0%, 0.1%, 0.2%, and 0.4%) on the dynamic properties of the MICP–fiber combined reinforced calcareous sand under small-strain conditions were studied using resonant column tests, scanning electron microscopy (SEM), and atomic force microscopy (AFM). The maximum dynamic shear modulus of the MICP–fiber combined reinforced calcareous sand under small-strain increases with the fiber content; the stiffness degradation rate of the dynamic shear modulus ratio of the test sample increases with the addition of two types of fibers, and the addition of hemp fibers greatly boosts the increase rate of the damping ratio. The SEM results indicate that excessive fibers distributed between the sand particles occupy the nucleation sites of bacteria, hinder the bonding between sand particles, and ultimately affect the dynamic shear modulus parameters of the sample. The AFM results show that the hemp fiber has much greater surface roughness than the polyester fiber. Therefore, the change rate of the damping ratio of the hemp fiber-doped MICP–fiber combined reinforced calcareous sand is much greater than that of the polyester fiber-doped sample. This is the first report on the basic mechanism of the small-strain dynamic properties of the MICP–fiber combined reinforced calcareous sand with different fiber contents and types. Furthermore, it provides a new theoretical basis for related research on improving the dynamic properties of sand thus reinforced.